The Effect of Temperature on Energy Use and CO₂ Emissions in the German Industry - Jakob Lehr; Katrin Rehdanz (ZBW - Leibniz Information Centre for Economics, 2021)
This paper adds to the scarce empirical evidence related to the impact of climate change on the manufacturing sector. To study the effect of temperature on energy use and CO2 emissions daily temperature information from 11.000 German municipalities are combined with the census of the manufacturing industry. The census data covers the universe of German manufacturing plants with more than 20 employees, close to 40.000 plants annually, and spans across more than two decades from 1995 to 2017. We find large and significant effects on CO2 emissions from cold days reflecting heating demand, while higher emissions from electricity consumption result from cooling needs. The increase in electricity related emissions from hot days is approximately twice as high among labor-intensive plants as it is among less labor-intensive plants. The response of direct emissions to cold days is roughly one third larger for old plants compared to new plants. When our estimates are combined with climate projections, direct emissions would decrease by about 12% by the end of the century due to rising temperatures under a business-as-usual scenario. The respective changes under the emission reduction scenario are about one-third of the changes under the business-as-usual scenario.
Keywords: Q41; Q53; D22; 330; Temperature; Climate Change; Manufacturing; Panel data; Energy use; Carbon emissions